Removal of Arsenic from Water Using a Composite of Iron–Manganese Oxide Incorporated Active Rice Husk Silica. Issue 4 (23rd February 2021) - Bui, Trung Huu; Pham, Van Sy; Thanh‐Nho, Nguyen; Trieu, Quoc An
Abstract: Low‐cost adsorbents from agricultural by‐products are intensively studied in water treatment, especially in arsenic removal for obtaining safe drinking water. Here, it is reported that a cheap and effective nano‐composite of iron–manganese oxide incorporated active rice husk silica (FMRS) for efficient removal of arsenic (As(III) and As(V)) from water, which is fabricated using a one‐pot synthesis. Fe 3+ and Mn 4+ in their oxides supported silica structure are successfully characterized. The FMRS ( q e  = 11.9 mg g −1 ) shows a remarkable enhancement of arsenic removal compared with the original rice husk ash ( q e  = 0.4 mg g −1 ) at initial [As(V)] = 5 mg L −1 . The As(III) and As(V) adsorption are in good agreement with both Langmuir and Freundlich non‐linear isotherm models ( R 2  > 0.98), where the maximum adsorption capacities at pH 7 are found up to 19.1 and 20.3 mg g −1, respectively. The role of Mn 4+ in enhancing the As(III) adsorption is also discussed. The FMRS exhibits high selectivity toward arsenic under the influences of other co‐existing anions in water (e.g., chloride, sulfate, and bicarbonate) and sustains a good arsenic removal efficiency during four cycles of the reusability test, suggesting a high potential of the fabricated adsorbent for long‐term removal of arsenic in field application. Abstract : A composite iron–manganese oxide incorporated active rice husk silica (FMRS) is successfully fabricated using a one‐pot process based on the simultaneous oxidation and co‐precipitation reactions of Fe(II) and Mn(VII) within the rice husk silica. The FMRS shows high adsorption capacity and selectivity toward As(III) and As(V). It implies a potential of this low‐cost adsorbent for field application.